Literature Review tentang Efektivitas Media Audiovisual dalam Pembelajaran Bahasa Arab: Analisis Sistematis terhadap Hasil Penelitian 5 Tahun Terakhir - Khairunnisa Slamat; Aisyah Hana' Zahida; Moh Abdul Kholiq Hasan (AKADEMIK: Jurnal Mahasiswa Humanis, 2026)
Arabic language learning in the digital era faces various challenges, such as low learning motivation, limited variety of teaching methods, and the need for more engaging and contextual media. Audiovisual media is a widely used alternative because it can present learning more concretely through a combination of sound, images, and visualizations, thus helping students understand the material more easily. This study aims to analyze the effectiveness of audiovisual media based on research trends over the past five years using the Systematic Literature Review (SLR) method. Data were collected through Google Scholar with the help of Publish or Perish and filtered using inclusion and exclusion criteria to obtain 36 articles eligible for analysis. Each article was reviewed based on the focus of media use, targeted language skills, learning outcomes, and reported challenges. The analysis results show that audiovisual media is effective in increasing motivation, attention, conceptual understanding, vocabulary mastery (mufrodat) and listening skills (maharah istimā’). The most widely used media type is video, followed by YouTube, animation, film, and other social media platforms. However, the use of audiovisual media for speaking (maharah kalām), conversation (muhādatsah), and writing (kitābah) skills remains limited. Challenges that often arise include suboptimal media quality, student reliance on visual materials, limited technological resources, and varying levels of teachers' digital competence. This study recommends improving teachers' abilities in designing simple audiovisual media, integrating them with active learning strategies, and utilizing alternative platforms in environments with limited facilities.